2001
DOI: 10.1111/1467-9817.00146
|View full text |Cite
|
Sign up to set email alerts
|

High school students’ literacy practices and identities, and the figured world of school

Abstract: Conventional wisdom holds that American teenagers do not read or write ± that they are a media-driven group who prefer movies, television and playing video games. Ethnographic data gathered in the High School Literacy Project, a study of four North Carolina high schools, showed a far different picture of teenage literacy. This paper reports on partial findings of the larger study and argues that students use their literacy practices to form their identities within, and sometimes in opposition to, the figured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…It is unclear why boys and girls differ in their attitudes toward reading. In their ethnographic study of high school students' literacy practices, Luttrell and Parker (2001) reported that boys believed that "reading and writing were 'girl' activities" (p. 237), suggesting one explanation for gender differences in reading attitudes. Although the result of the MANOVA indicated no differences in reading attitude among the three reading ability groups, a notable trend emerged among reading ability levels when only the boys were considered, a trend that did not emerge when only girls were considered.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why boys and girls differ in their attitudes toward reading. In their ethnographic study of high school students' literacy practices, Luttrell and Parker (2001) reported that boys believed that "reading and writing were 'girl' activities" (p. 237), suggesting one explanation for gender differences in reading attitudes. Although the result of the MANOVA indicated no differences in reading attitude among the three reading ability groups, a notable trend emerged among reading ability levels when only the boys were considered, a trend that did not emerge when only girls were considered.…”
Section: Discussionmentioning
confidence: 99%
“…In an introduction to the Urban Review's special issue on the ways in which figured worlds enable educational researchers to explore "sociocultural constructs in education" [16], an emphasis is placed upon how worlds can be reimagined by marginal student groups reappropriating the discourse that seeks to position them. More specific to literacy [17], evidence is presented as to how teachers can open up a space to harness high school students' home literacy practices and refigure the world of literacy in their school.…”
Section: Identity and Hegemonic Masculinitymentioning
confidence: 99%
“…Earlier sociological work [17,18] highlights the ways in which teachers perpetuate gender inequalities through the language they use with their in pupils in school. Indeed, the ways in which the teachers are either complicit or dominant in participating in gender stereotyping is in line with Connell's concept of "hegem-onic masculinity": "a pattern of practices" that allow "men's dominance over women to continue" [13:832].…”
Section: Identity and Hegemonic Masculinitymentioning
confidence: 99%
“…Some scholars doing research in education, however, have used figured worlds or related concepts in different ways each contributing further to the usefulness of this concept in studying identity, agency, and contexts in education (Bartlett, 2007;Blackburn, 2003;Boaler & Greeno, 2000;Dagnais, Day, & Toohey, 2006;Jurow, 2005;Leander, 2002;Luttrell & Parker, 2001;Street, 2003;Wortham, 2004Wortham, , 2006Urrieta, 2006). I will not delve deeply into the literature here because Rubin (this issue) does a good job of reviewing that literature in her piece.…”
Section: Figured Worlds and Education: The Special Issuementioning
confidence: 99%
“…Luttrell and Parker (2001) for example used the concept of figured worlds to study high school studentsÕ literacy practices against the larger constructs of school, work and family. Their findings on youthÕs literacy practices serve as a springboard to question the veracity and legitimacy of the often taken-forgranted notions of what literacy means and what it entails in the various worlds of school, family, and work.…”
Section: Figured Worlds and Education: The Special Issuementioning
confidence: 99%